Pharmacoepidemiology of Drug Exposure in Intubated and Non-Intubated Preterm Infants With Severe Bronchopulmonary Dysplasia - Lewis, T.; Truog, W.; Nelin, L.; Napolitano, N.; McKinney, R. L.; , and on behalf of The BPD Collaborative (Frontiers in Pharmacology, 2021)
Background: Infants with severe bronchopulmonary dysplasia (BPD) are commonly treated with off-label drugs due to lack of approved therapies. To prioritize drugs for rigorous efficacy and safety testing, it is important to describe exposure patterns in this population. Objective: Our objective was to compare rates of drug exposure between preterm infants with severe bronchopulmonary dysplasia based on respiratory support status at or beyond 36 weeks post-menstrual age. Methods: A cross-sectional cohort study was performed on October 29, 2019. Preterm infants with severe BPD were eligible and details of respiratory support and drug therapy were recorded. Wilcoxon paired signed rank test was used to compare continuous variables between the invasive and non-invasive groups. Fisher’s exact test was used to compare binary variables by respiratory support status. Results: 187 infants were eligible for the study at 16 sites. Diuretics were the drug class that most subjects were receiving on the day of study comprising 54% of the entire cohort, followed by inhaled steroids (47%) and short-acting bronchodilators (42%). Infants who were invasively ventilated (verses on non-invasive support) were significantly more likely to be receiving diuretics (p 0.013), short-acting bronchodilators (p < 0.01), long-acting bronchodilators (p < 0.01), systemic steroids (p < 0.01), systemic pulmonary hypertension drugs (p < 0.01), and inhaled nitric oxide (p < 0.01). Conclusion: Infant with severe BPD, especially those who remain on invasive ventilation at 36 weeks, are routinely exposed to multiple drug classes despite insufficient pharmacokinetic, safety, and efficacy evaluations. This study helps prioritize sub-populations, drugs and drug classes for future study.